Análise não linear de compósitos laminados utilizando o método dos elementos finitos - Dantas Júnior, Edson Moreira (2014)
Composite materials has been widely studied thought the years because of it benefits compared to metals (elevated resistance/weight ratio, good thermal isolation and good fatigue resistance). Laminate composites are the focus of this work. Produced by stacked layers of fibers embed- ded on polymeric matrices, structures of composite materials presents material and geometrical non-linear behavior. Because of it elevated resistance, composite materials allow designers to create very slender structures which might present large displacements and stability problems. Additionally, considering material non-linearity is also important for collapse simulation of la- minated structures. One of the most important failure modes on laminated structures is delami- nation. Delamination is the detachment of adjacent layers. On laminated structures simulation, the Finite Element Method is one of the most used analysis tool. It is a robust, precise and relative simple operating tool. Intending analyzing non-linear behavior of laminated structures subjected to large displacements, was developed on this work a laminated solid finite element formulation based on Full Lagrangian formulation. Simulation of delamination beginning and propagation was developed on this work using Cohesive Zone models. To achieve this goal, an isoparametric formulation of interface finite elements without thickness and many constitutive models to represent the relation tension × displacement jump (relative displacement between crack faces) were developed. These models consider pure mode I and mixed mode. The formu- lations developed on this work were implemented on the open source finite element code FAST using Oriented Object Programing philosophy. These implementations are presented on UML conventions. Many examples were tested for verifying and validating all the implementations. Excellent results were obtained using laminated solid elements on the analysis of a shell struc- ture, even using meshes with only one element though thickness. On the delamination analysis, was verified that Cohesive Zone Models are very sensible related to the parameters used on the analysis, mainly tension × displacement jump model, size of elements and numerical integra- tion. Spite of it, using Newton-Cotes integration and interface elements of appropriate size, good agreements were obtained compared with theoretical results obtained on literature. In general, was observed that cohesive exponential model presents greater robustness and compu- tational efficiency than bilinear model